Evaluation of the Corrosion Behavior of the Al-356 Alloy in NaCl Solutions (2011)
Cellular metals are a new class of materials with promising applications and a unique combination of physical, chemical and mechanical properties. The Al-356 alloy is used to manufacture metal foams from NaCl preforms. Despite the usefulness of these materials, their performance may be affected by corrosion due to residual salt. This paper reports the study of the behavior of the Al356 alloy in chloride solutions by electrochemical techniques in rotating disk electrode. The cathodic reaction of oxygen reduction is the crucial stage of process dissolution of the material, which shows that is the oxygen transport which limits the corrosion process.